FRI0110 Bowel perforation in systemic lupus erithematosus. (1st June 2001) - Pombo, ME; Diez, L; Bernardino, JI; García, F; Mora, M; Lavilla, P; Gil, A
Abstract : Background: Objectives: Bowel perforation is a rare but serious complication in SLE. Although several processes not related to SLE (diverticulitis, tumours) may be the cause of this complication, it has been previously considered to be associated to small-vessel vasculitis in active lupus disease. Nowadays, a vascular damage induced by antiphospholipid antibodies (aPL) and steroids seems to play an important role. Methods: Seven patients with intestinal perforation were observed in 220 SLE patients during a period of 26 years (1974–2000). In all cases, the diagnosis of intestinal perforation was confirmed by surgery or autopsy and pathological examination. Results: All patients were females, with a mean age at the diagnoses of bowel perforation of 45 years, and a mean time of SLE evolution of 13 years. The site of perforation was in the colon in 4 patients and in the small bowel in the other 3. Six patients had lupus nephropathy, one of them with renal transplantation. Central nervous system and cutaneous involvement was observed in 4 patients and Sjögren's syndrome, Libman-Sachs endocarditis and haemolytic anaemia in two patients. aPL were present in 5 patients. All patients were on steroid therapy at the moment of the intestinal perforation. Abdominal pain was present in all cases but the mean time of diagnosis delay was 11 days. Two patients died from peritonitis and septic shock. A local cause of perforation was found in four patients: diverticulitis (3) and adenocarcinoma of the rectum (1). Necrotizing vasculitis was not observed in any case of pathological examinations. Conclusion: Bowel perforation, although uncommon in SLE, has to be taken into account as a differential diagnosis in a patient with abdominal pain. Disease severity, antiphospholipid antibodies and previous steroid therapy are important risk factors for this complication.